Triglycerides and glucose index as an insulin resistance marker in a sample of healthy adults - Toro Huamanchumo, Carlos J. (2018)
Aim: To assess the association between elevated triglycerides/glucose index (TGI) and insulin resistance (IR) or hyperinsulinemia after oral glucose tolerance test (OGTT) in a sample of healthy adults. Methods: We conducted an analytical cross-sectional study in euthyroid non-diabetic adults, who attended the outpatient service of a private clinic in Lima-Peru during the 2012–2016 period. Participants were categorized in two groups according to the presence or absence of elevated TGI, IR or hyperinsulinemia after OGTT. A TGI value ≥ 8.65 was considered as elevated. We defined IR as a Homeostasis Model Assessment (HOMA-IR) value ≥ 2.28 and hyperinsulinemia after OGTT as a serum insulin value ≥ 80μU/mL after 120 min of 75-g glucose intake. We elaborated crude and adjusted Poisson regression models to assess the association between elevated TGI and IR or hyperinsulinemia after OGTT. The reported association measure was the prevalence ratio (PR) with their respective 95% confidence intervals (95%CI). Results: We analyzed 118 individuals, the average age was 37.5 ± 11.3 years, 21 (17.8%) were males and the median BMI was 22.7 ± 1.6 kg/m2. The prevalence of elevated TGI was 25.4% (n=30) while the prevalence of IR and hyperinsulinemia after OGTT was 24.6% (n=29) and 17.0% (n=20) respectively. In the adjusted model, elevated TGI was associated with both IR (aPR=6.36; 95%CI: 3.41–11.86) and hyperinsulinemia after OGTT (aPR=4.19; 95%CI: 1.81–9.70). Conclusions: We found that elevated TGI was associated with both IR markers in a sample of euthyroid adults without T2DM and with a normal BMI. The simplicity of the TGI calculation makes it the first-choice alternative when the hyperinsulinemic-euglycemic clamp or HOMA-IR are not available. © 2018 Diabetes India